The prevalence and survival of children with congenital septal defects in the UK using CPRD - Onuwe, Toluwalope Yetunde (2022)
Background Congenital heart disease (CHD) is a major contributor to infant mortality worldwide, accounting for a third of total congenital defects and a fifth of total global early neonatal mortality. Congenital septal defects (SD) are the most common CHD. This study assesses the prevalence and survival of children diagnosed with congenital septal defects in the UK.